Implementasi Sistem Operasional Pelayanan Tour Leader dalam Meningkatkan Kualitas Layanan Jamaah Umrah (Studi pada PT. Wafdullah Tamu Mulia Cabang Bengkulu) - Dyana Karlina; Khairiah Elwardah; Evan Stiawan (Universitas Muhammadiyah Surabaya, 2026)
This study aims to determine the implementation of the operational system of tour leader services and the quality of services for Umrah pilgrims at PT. Wafdullah Tamu Mulia Bengkulu Branch. This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through interviews, observations, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the operational system of tour leader services has been running quite effectively, as seen from the implementation of pre-departure briefings, supported by qualified human resources, the availability of adequate facilities, implementing programs in accordance with established SOPs, and being able to provide comfort to pilgrims. However, there are still obstacles in conveying communication with elderly pilgrims and the limited number of tour leaders and accompanying staff. The quality of services for Umrah pilgrims as a whole is good, this is indicated by the availability of adequate physical facilities, the accuracy of activity schedules, the smooth implementation of worship, the alertness of tour leaders in responding to the needs and emergency conditions of pilgrims, as well as a friendly, patient, and caring attitude, especially to elderly pilgrims. Tour leaders also have competence and professionalism in guiding the implementation of Umrah worship, so as to foster pilgrims' trust in the quality of services provided.